ACADEMIC SUPERVISION AS AN EFFORT TO IMPROVE TEACHER TEACHING QUALITY AND STUDENT LEARNING OUTCOMES AT BABUSSALAM BESILAM PRIVATE TSANAWIYAH MADRASAH - Hannum, Ikhsanti (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research discusses the academic supervision carried out by the Madrasah supervisor for teachers at the private Babussalam Besilam Tsanawiyah Madrasah. The aim is to explain how the implementation of supervision activities can improve the quality of teaching and student learning outcomes in the Madrasah, in the 2022/2023 academic year. The main focus of the research is the preparation of learning planning tools that must be made by teachers. The use of steps divided into three cycles as the main way to collect data. This method is certainly a characteristic of the type of qualitative research using the School Action Research (PTS) approach. Product moment analysis and t test as a way to manage and analyze data, with 15 teachers used as samples. The ability to prepare learning plans and learning components is an assessed criterion. The results of the research were that in cycle I the validity value of the teacher's learning planning ability was 0.730 and the learning components were 0.713, while the t test value of the teacher's learning planning abilities was 3.856 and the learning components were 1.759. In calculating the second cycle against the third cycle, the validity value of the teacher's learning planning ability was 0.911 and the learning component was 0.906, with a t test of 7,948 for the teacher's learning planning ability) and 3,701 for the learning planning component. For teacher pedagogical competence, the average score for 15 subjects in the initial activities in the first cycle to the second cycle was 0.690 for validity and 3.438 for the t test. Meanwhile, in the second cycle and the third cycle, the validity value of the initial learning activities reached 0.883 and the t test value reached 6.773. These results indicate a significant increase in teacher abilities.